Derivative Operators on Quantum Space(3) with Two Parameters and Weyl Algebra - Ozavsar, Muttalip; Yesilot, Gursel (EUROPEAN JOURNAL PURE & APPLIED MATHEMATICS, 2012)
In this paper, we introduced a quantum space generated by three noncommutative coordinates with two commutation parameters. We also give a Hopf algebra structure in order to construct a bicovariant differential calculus over this quantum space. Morever, it is shown that noncommutative derivative operators corresponding to the coordinates comprise a Weyl algebra deformed by the commutation parameters.
Keywords: Hopf Algebras; Quantum Spaces; Weyl Algebra; Mathematics